Speed and Lateral Inhibition of Stimulus Processing Contribute to Individual Differences in Stroop-Task Performance - Naber, Marnix; Vedder, Anneke; Brown, Stephen B. R. E.; Nieuwenhuis, Sander (Frontiers in Psychology, 2016)
The Stroop task is a popular neuropsychological test that measures executive control. Strong Stroop interference is commonly interpreted in neuropsychology as a diagnostic marker of an impairment in executive control, possibly reflecting executive dysfunction. However, popular models of the Stroop task indicate that several other aspects of colour and word processing may also account for individual differences in the Stroop task, independent of executive control. Here we use new approaches to investigate the degree to which individual differences in Stroop interference correlate with the relative processing speed of word and colour stimuli, and the lateral inhibition between visual stimuli. We conducted an electrophysiological and behavioural experiment to measure (1) how quickly an individual’s brain processes words and colours presented in isolation (P3 latency), and (2) the strength of an individual’s lateral inhibition between visual representations with a visual illusion. Both measures explained at least 40% of the variance in Stroop interference across individuals. As these measures were obtained in contexts not requiring any executive control, we conclude that the Stroop effect also measures an individual’s pre-set way of processing visual features such as words and colours. This study highlights the important contributions of stimulus processing speed and lateral inhibition to individual differences in Stroop interference, and challenges the general view that the Stroop task primarily assesses executive control.